Diamond-P-vCube: An Eventually Perfect Hierarchical Failure Detector for Asynchronous Distributed Systems - Stein, Gabriela; Rodrigues, Luiz Antonio; Duarte Jr., Elias Procópio; Arantes, Luciana (Anais do Latin-American Symposium on Dependable Computing (LADC); 2023: Anais do XII Latin-American Symposium on Dependable Computing, 2023)
In this work, we introduce ◊P-vCube, a push-based failure detector for asynchronous distributed systems. Processes running ◊P-vCube are hierarchically organized on the vCube virtual topology, which presents several logarithmic properties. As there are no bounds on communication delays and process execution times, false suspicions may occur. To ensure eventual accuracy, a process exits the system when it learns that it has been suspected by another process or suspects every other process. We show that ◊P-vCube guarantees completeness in any situation, and eventual accuracy if all correct processes remain strongly connected among themselves. We implemented the proposed algorithm using simulation and presented comparison results with the traditional all-test-all solution and a ring approach. The results demonstrate the trade-off between the speed of detecting actual failures and the number of messages used, as well as the scalability of ◊P-vCube.